Bői Közös Önkormányzati Hivatalhoz tartozó települések helyi adóztatási gyakorlatának összehasonlító elemzése. - Németh Anett (2019)
The aim of my thesis is to introduce the inland revenues of those townships which belong to the Common Town-hall of Bő and belong to my everyday work. At the beginning I panned out about the formation of local governments as well. The subsystem of the local governments was actually laid down in the act of the 1990s. At the formation of the local governments I took the paragraphs of the Fundamental law into account which I put a premium on for the sake of the approach and demonstration. An illustration of the hierarchy of the local governments was made by me as well to made the structure of local governments clearer. At the beginning I panned out about the formation of local governments as well. The subsystem of the local governments was actually laid down in the act of the 1990s. At the formation of the local governments I took the paragraphs of the Fundamental law into account which I put a premium on for the sake of the approach and demonstration. An illustration of the hierarchy of the local governments was made by me as well to made the structure of local governments clearer. Everything is not obvious because it is not all the same that we talk about ratepayer or taxpayer. The different tax categories were grouped and introduced in detail one by one by me. The law gives the opportunity to the local governments to regulate the inland revenues. In particular cases it could give exemptions and reductions. Of course it could assign exemption in regulation but just such, other rule of law doesn't prohibit or regulate. As I introduced in my thesis, at the moment 10 townships belong to the Common Town-hall of Bő, which headquarters is Bő. Then I took stock of the basic details of the certain local governments and I scheduled and introduced the taxes which were introduced in the certain townships. For a 5 years period I had a look at the inland revenues of the certain townships respectively those rates compared to the total income. On the basis of the calculated details surprising results were born. In the case of several townships it is noticeable that they have less inland revenue as compared to the population as we had concluded before. I took into consideration of the assets which were shown at the six months closing. I also introduced the recovery work of the local governments. There are several opportunities of the local governments to their recovery work, which I also mentioned.